2013
DOI: 10.2147/jpr.s46553
|View full text |Cite
|
Sign up to set email alerts
|

Population-based study of central post-stroke pain in Rimini district, Italy

Abstract: Central post-stroke pain (CPSP) is still an underestimated complication of stroke, resulting in impaired quality of life and, in addition to the functional and cognitive consequences of stroke, the presence of CPSP may be associated with mood disorders, such as depression, anxiety, and sleep disturbances. This type of pain may also impair activities of daily living and further worsen quality of life, negatively influencing the rehabilitation process. The prevalence of CSPS in the literature is highly variable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…This was the expected result; CPSP affected the physical function, pain, and physical score components of the SF-36 QoLS poorly, but the other components of the SF-36 QoLS were not affected in our patients. Previous studies showed that CPSP affected not only physical functions but also mental functions poorly 26 , 27 , 28 ) . We thought that this difference was due to the protocol of our study which was a controlled study.…”
Section: Discussionmentioning
confidence: 99%
“…This was the expected result; CPSP affected the physical function, pain, and physical score components of the SF-36 QoLS poorly, but the other components of the SF-36 QoLS were not affected in our patients. Previous studies showed that CPSP affected not only physical functions but also mental functions poorly 26 , 27 , 28 ) . We thought that this difference was due to the protocol of our study which was a controlled study.…”
Section: Discussionmentioning
confidence: 99%
“…CPSP has been identified in 1%–50% of total patients after stroke of both IS and ICH origins [7,1317] ; however, CPSP is more common in patients with a thalamic stroke, and varies from 11% to 32% [1823] . CPSP patients most often present with spontaneous and/or evoked pain (hyperalgesia and allodynia) or paresthesia/dysesthesia in a persistent and/ or paroxysmal form [5–7,24] .…”
Section: Introductionmentioning
confidence: 99%
“…Neuropathic pain refers to the douleur anormale (abnormal pain), caused by damage and dysfunction of the central or peripheral nervous system [1,2]. Neuropathic pain is one type of chronic pain, whose main clinical manifestations include hyperalgesia, paresthesia, ambulatory pain and allodynia [3,4]. According to statistics, the prevalence rate is 0.6-1.5% and with the aging of the population, the prevalence rate increases gradually [5].…”
Section: Introductionmentioning
confidence: 99%